Sosialisasi Penggunaan Website dan Aplikasi Halal MUI terhadap Keputusan Pembelian pada Wali Murid TK Sartika: Socialization of the Use MUI Halal Website and Application on Purchasing Decisions of Students’ Guardian in TK Sartika - Astuti, Nugrahani; Sari, Fitri Komala; Muyasyaroh, Hidayatun; Nurfatimah, Ratna Palupi; Hutauruk, Janu; Inayati, Dyah Ajeng Tsinta; Mawarni, Mega Adi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The halalness of food products is an important concern for the Muslim community, especially for guardians who are responsible for their children’s consumption. Majelis Ulama Indonesia (MUI) has provided a halal certification checking facility through the MUI Halal website and application. However, many people still do not understand how to use it, so socialization is needed to increase awareness in choosing halal products. The purpose is to improve the understanding and skills of Sartika Kindergarten, Ketintang Surabaya guardians in checking the halal certification of food and beverage products through the MUI Halal website and application. Socialization is expected to help students’ parents make decisions about purchasing halal products so that they are more focused and in accordance with Islamic law. The Activity Implementation Method is carried out through three stages: (1) coordination with the school, (2) socialization and training in the use of the MUI Halal website and application, and (3) evaluation by filling out a questionnaire. The results of this Socialization Activity significantly increased the participants’ understanding. Before the activity, three respondents agreed to check the halal certification before buying a product, while after the socialization and training, there was an increase in the number of respondents who answered strongly agree, namely 18 respondents. This shows the effectiveness of socialization in increasing awareness and purchasing decisions for halal products.